2019
DOI: 10.1002/msc.1393
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in children with early‐stage juvenile idiopathic arthritis

Abstract: Background Juvenile idiopathic arthritis (JIA) is a chronic inflammatory disease resulting in physical and psychological disability. This study aimed to measure the health‐related quality of life (HRQOL) and identify factors influencing the HRQOL. Methods We conducted a cross‐sectional study in Thai children with JIA and their parents between January and December 2015, using the Thai version of the Pediatrics Quality of Life (PedsQL) 4.0 generic core scale. Results Sixty‐five children (33 girls and 32 boys) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
5
0
6
Order By: Relevance
“…When looking at the presence of SEs and their severity, we can note a clear impact on HRQoL. The lowered HRQoL of JIA patients has been previously established (2,27,28), and our study suggests that SEs play a role in this lowered HRQoL. Brunner et al showed that patients with a GISSK score of ≥2 had a significantly lower HRQoL than others without GI symptoms but similar disease activity (20).…”
Section: Discussionsupporting
confidence: 74%
“…When looking at the presence of SEs and their severity, we can note a clear impact on HRQoL. The lowered HRQoL of JIA patients has been previously established (2,27,28), and our study suggests that SEs play a role in this lowered HRQoL. Brunner et al showed that patients with a GISSK score of ≥2 had a significantly lower HRQoL than others without GI symptoms but similar disease activity (20).…”
Section: Discussionsupporting
confidence: 74%
“…Зважаючи на період, за який аналізувалися статті, більшість із них містила або інформацію з культурної адаптації валідизованих опитувальників, або подавала огляд проблеми оцінки якості життя. Але всі автори відзначають суттєве зниження показників якості життя у дітей з ЮІА [28][29][30][31][32].…”
Section: результати та обговоренняunclassified
“…У тайландському дослідженні, яке мало за мету оцінку якості життя, пов'язану зі здоров'ям дітей з ЮІА, автори відзначають, що отримані результати збігаються із загальновідомими щодо зниження якості життя таких дітей. Також збігаються дані щодо оцінки результатів шкали фізичного функціонування, через що автори рекомендували належним чи-ном відслідковувати ЯЖ дітей з ЮІА за допомогою PedsQL загального профілю та звертати особливу увагу на пацієнтів із субоптимальним показником якості життя [32].…”
Section: рисунок 1 діаграма публікацій щодо оцінки якості життя у популяції загаломunclassified
“…Consequently, there is a growing consensus among researchers and clinicians that ameliorating patient symptoms and improving HRQOL are the primary goals of the management of JIA ( 9 , 11 ). The constant monitoring of the JIA course (such as disease manifestations, therapies effects, morbidities, functional status, and quality of life) is a key way to achieve the goals.…”
Section: Introductionmentioning
confidence: 99%